Trisomy 15 mosaicism in an IVF fetus. Issue 10 (October 1992) - Bennett, C P; Davis, T; Seller, M J
Abstract : Prenatal diagnosis of an IVF pregnancy in a woman aged 41 years showed a fetus mosaic for trisomy 15. The fetus had dysmorphic features, hypoplastic adrenal glands, and an accessory spleen. Both IVF and advanced maternal age would seem to increase the risk of trisomy 15.